The Association between Peak Resultant Linear Acceleration and Brain Tissue Deformation in American Football-related Helmeted Head Impacts - Zanetti, Katrina (Université d'Ottawa / University of Ottawa, 2014)
The objective of this study was to determine the degree of association of peak resultant linear acceleration with maximum principal strain, von Mises stress, and strain rate in the cerebrum. Three prevalent head impact mechanisms in the sport of football were represented by impacting an accelerometer-outfitted Hybrid III headform. Head to head impacts were characterized using a linear impactor, falls to the ground using a monorail drop, and elbow or forearm strikes to the head by a pendulum system. Representative inbound impact velocities were selected according to epidemiological research. Impacts were performed at nine prescribed centric and non-centric sites on the head. Finite element modeling using the University College Brain Trauma Model was employed to obtain peak values of maximum principal strain, von Mises stress, and strain rate in the cerebrum. Pearson product-moment correlation coefficients (r) were calculated between peak resultant linear acceleration of the head and peak MPS, VMS, and strain rate in order to determine the degree of correlation between the variables. This was determined for each impact mechanism and location as well as for all mechanisms together. Significant correlations (p<0.05) between peak linear acceleration and the three metrics of tissue deformation were found for particular mechanisms of impact. For each of MPS, VMS, and strain rate, impacts conducted on the pendulum system, meant to replicate arm to head impacts, did not have a significant correlation with linear acceleration. In contrast, the head to head mechanism of impact resulted in significant correlation coefficients between linear acceleration and all metrics of tissue deformation. The strength of the correlation was not significantly different when centric versus non-centric impact sites were compared. Overall, characteristics of a head impact such as the inbound energy, whether the vector of impact was centric or non-centric, and the degree of energy transfer that occurs through the head upon impact, likely play a role in the resulting degree of correlation between linear acceleration and brain tissue deformation.